PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA, DAN BEBAN KERJA, TERHADAP KINERJA KARYAWAN PADA PT. BANDAR RAYA MUARA ABADI - William Wijaya; Winni Winni; Cut Fitri Rostina; Yusuf Ronny Edward; Fauzi Fauzi (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
This study aims to determine the effect of leadership style, work environment, and workload on employee performance at PT. Bandar Raya Muara Abadi. This study used a quantitative approach with a survey method through the distribution of questionnaires to employees. The population in this study amounted to 35 people, with the sampling technique using a saturated sampling method so that the entire population served as respondents. The data analysis technique used was multiple linear regression analysis with the assistance of a statistical program. The results showed that, partially, leadership style had a positive and significant effect on employee performance with a calculated t-value of 5.816 and a significance of 0.000 <0.05. The work environment had a positive and significant effect on employee performance with a calculated t-value of 7.871 and a significance of 0.000 <0.05, and was the most dominant variable. Workload also had a positive and significant effect on employee performance with a calculated t-value of 4.783 and a significance of 0.000 <0.05. Simultaneously, leadership style, work environment, and workload significantly influence employee performance, with a calculated F-value of 119.211 and a significance level of 0.000 < 0.05. The coefficient of determination (Adjusted R Square) of 0.913 indicates that 91.3% of the variation in employee performance can be explained by the three independent variables, while the remaining 8% is influenced by factors outside the research model.